Synthesis of Cyano-Benzylidene Xanthene Synthons Using a Diprotic Brønsted Acid Catalyst, and Their Application as Efficient Inhibitors of Aluminum Corrosion in Alkaline Solutions - Amin, Mohammed A.; Mersal, Gaber A. M.; El-Hendawy, Morad M.; Shaltout, Abdallah A.; Badawi, Ali; Boman, Johan; Gobouri, Adil A.; Saracoglu, Murat; Kandemirli, Fatma; Boukherroub, Rabah; Ryl, Jacek; Khalifa, Mohamed E. (MDPI AG, 2022)
Novel cyano-benzylidene xanthene derivatives were synthesized using one-pot and condensation reactions. A diprotic Brønsted acid (i.e., oxalic acid) was used as an effective catalyst for the promotion of the synthesis process of the new starting xanthene–aldehyde compound. Different xanthene concentrations (ca. 0.1–2.0 mM) were applied as corrosion inhibitors to control the alkaline uniform corrosion of aluminum. Measurements were conducted in 1.0 M NaOH solution using Tafel extrapolation and linear polarization resistance (LPR) methods. The investigated xanthenes acted as mixed-type inhibitors that primarily affect the anodic process. Their inhibition efficiency values were enhanced with inhibitor concentration, and varied according to their chemical structures. At a concentration of 2.0 mM, the best-performing studied xanthene derivative recorded maximum inhibition efficiency values of 98.9% (calculated via the Tafel extrapolation method) and 98.4% (estimated via the LPR method). Scanning electron microscopy (SEM) was used to examine the morphology of the corroded and inhibited aluminum surfaces, revealing strong inhibitory action of each studied compound. High-resolution X-ray photoelectron spectroscopy (XPS) profiles validated the inhibitor compounds’ adsorption on the Al surface. Density functional theory (DFT) and Monte Carlo simulations were applied to investigate the distinction of the anticorrosive behavior among the studied xanthenes toward the Al (111) surface. The non-planarity of xanthenes and the presence of the nitrile group were the key players in the adsorption process. A match between the experimental and theoretical findings was evidenced.
Keywords: Organic chemistry; [CHIM.ORGA] Chemical Sciences/Organic chemistry; DFT; inhibition; Article; Monte Carlo simulations; Corrosion; [CHIM.THEO] Chemical Sciences/Theoretical and/or physical chemistry; QD241-441; Xanthenes; xanthene dyes; Adsorption; dimedone; xanthene dyes; dimedone; aluminum corrosion; inhibition; DFT; Monte Carlo simulations; Acids; aluminum corrosion; Aluminum